Legal Protection for Child Victims of Bullying Resulting in Death (Case Study at the South Bangka Police) - Bagas Dyas Maula; Ira Alia Maerani (Law Development Journal, 2026)
This study aims to analyze the causal factors of child bullying resulting in death and to examine legal protection for victims under Indonesian positive law through a case study of case handling at the South Bangka Police Resort in order to formulate just policy recommendations. Legal protection is still suboptimal, requiring strengthened coordination and protection policies. This study uses the Legal Protection Theory to assess the fulfillment of victims' rights, John Rawls's Theory of Justice as the basis for substantive justice analysis, and the theory of maqāṣid al-syarī‘ah to examine the protection of children's lives and welfare. These three theories provide a comprehensive framework for evaluating the effectiveness of legal protection that is comprehensive, responsive, proportional, victim-oriented, and child-oriented.